2016
DOI: 10.1002/oby.21676
|View full text |Cite
|
Sign up to set email alerts
|

Family factors that characterize adolescents with severe obesity and their role in weight loss surgery outcomes

Abstract: Objective To comprehensively assess family characteristics of adolescents with severe obesity and whether family factors impact weight loss outcomes following weight loss surgery (WLS). Methods Multi-site prospective data from 138 adolescents undergoing WLS and primary caregivers (Adolescent Mage=16.9; MBMI= 51.5 kg/m2; Caregiver: Mage=44.5; 93% female) and 83 non-surgical comparators (NSComp: Adolescent: Mage=16.1; MBMI= 46.9 kg/m2; Caregiver: Mage=43.9; 94% female) were collected using standardized measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…Factors previously found to predict attrition from adolescent behavioral weight management programs such as family stressors and maternal distress were not significant predictors in this study. A recent study found that family dysfunction was unrelated to weight loss outcomes in adolescents post-surgery [17] and suggested that, despite exhibiting clinically significant family dysfunction, some adolescents still completed surgery, which may explain the current findings. It is also possible that families reporting higher rates of communication problems and emotional conflict prior to surgery may opt out of the procedure due to added strain on the family.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Factors previously found to predict attrition from adolescent behavioral weight management programs such as family stressors and maternal distress were not significant predictors in this study. A recent study found that family dysfunction was unrelated to weight loss outcomes in adolescents post-surgery [17] and suggested that, despite exhibiting clinically significant family dysfunction, some adolescents still completed surgery, which may explain the current findings. It is also possible that families reporting higher rates of communication problems and emotional conflict prior to surgery may opt out of the procedure due to added strain on the family.…”
Section: Discussionmentioning
confidence: 70%
“…The present paper also adds to an emerging literature highlighting the occurrence of bariatric surgery in multiple generations within a household [17, 28, 29]. The risks and benefits of caregiver bariatric surgery on adolescent patient bariatric surgery outcomes are unknown, although this is an anticipated area of investigation within the Teen-LABS consortium and associated ancillaries [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither patient‐related preoperative features, including eating disorders and affective disorders, nor family‐related factors, such as caregiver weight status or family dysfunction, clearly contribute to poorer outcomes. However, adolescent perceptions of improved family communication and emotional climate are associated with improved weight loss 62 . When weight regain is a concern, behavioral support as well as food tracking may be useful in addressing these behaviors 33…”
Section: Postoperative Managementmentioning
confidence: 99%
“…Additionally, the samples from these 17 studies were drawn from diverse locations, including primary care, community settings, and paediatric weight management programs. Zeller et al also assessed family functioning among adolescents in weight management and adolescents receiving bariatric surgery, where approximately 32% of families met criteria for impaired family functioning based on the clinical cutoff score. In population‐level data, adolescents with healthier family functioning, assessed by the FAD, had healthier diet and physical activity behaviours and weight status .…”
Section: Introductionmentioning
confidence: 99%